The influence of normal, pathological and psychological factors on postural reactions to multidirectional perturbations - Carpenter, Mark Gregory (University of Waterloo, 2001)
This thesis constitutes a series of 4 studies which examined the physiological mechanisms involved in recovering balance from an unexpected perturbation to upright stance in humans. Postural reactions to unexpected falls are typically probed through manipulations of support surface characteristics, such as tilting rotations or sliding translations of the support surface. In the past, these perturbations have been applied almost exclusively in a single pitch (forward/backward) direction. However, outside of the laboratory we stumble, become shifted or bumped in many directions and not just in the pitch plane. The main objective of this thesis was to extend the current understanding of how humans recover from perturbations which might lead to falls in the pitch direction, to multiple directions which may mimic more normal postural challenges faced in daily life. Our first study examined normal response characteristics of healthy young controls recovering from unexpected pitch and roll combinations of surface rotations in 16 different directions. The results revealed distinct muscle response characteristics of both early stretch and later balance correcting responses which were highly sensitive to the direction of perturbation. Trunk muscles in particular were found to provide early directionally sensitive proprioceptive information on roll perturbations. Trunk motion occurred earlier in the roll compared to the pitch direction. These findings verified the importance of examining postural reactions in multiple directions and highlighted the role of proximal muscles involved in control of the trunk and hip joint. Previous studies examining the effects of either peripheral balance deficits such as vestibular loss or central disorders such as Parkinson's disease have had varied and inconsistent results. We hypothesized that the lack of agreement between studies and poor discriminatory ability of dynamic posturography to identify patients with balance deficits may have stemmed from the inability to observe roll directed instability in these populations. We performed two different studies to examine how bilateral peripheral vestibular loss and Parkinson's disease (PD) influenced postural reactions to perturbations in multiple directions. We have examined our results with two underlying themes. First to determine whether previous findings based on pure pitch plane research can be extended to directions other than the pitch plane. Second, what new information can be yielded from multi-directional perturbations which is not available from observations restricted in the pitch plane. In patients with compensated bilateral peripheral vestibular loss, we observed differences in amplitude modulation of both leg and trunk muscle balance correcting activity, and particularly abnormal control of the trunk in the pitch and roll directions which were not previously observed using only pitch plane perturbations. As a result we hypothesized that roll and pitch control is separately programmed by the central nervous system. PD patients had impaired gain control of both stretch and subsequent balance correcting responses in lower leg, hip and trunk muscles. This was compounded by a loss of directional sensitivity in soleus and paraspinals, which led to co-contraction and stiffening of the ankle and trunk. Leg and trunk abnormalities were poorly compensated by protective arm movements which were reduced in amplitude and improperly tuned to the direction of the perturbation. Abnormalities in PD patients became most prominent when perturbations were backward and to the side. Although some of the abnormalities were clearly due to the disease itself, some may have also been related to medication effects and other factors such as increased fear of falling. Previous studies have shown that fear of falling can influence other aspects of balance control including quiet standing, and anticipatory postural adjustments preceding a voluntary movement. The final study of the thesis was directed at identifying which components of a normal postural reaction are susceptible to a confounding influence of fear of falling. We found that both the amplitude of the balance correcting response as well as the directional sensitivity of some postural muscles was significantly influenced by an increase in postural threat. These alterations in muscle responses were expressed in significant changes in knee and trunk control as well as protective arm movements when standing under increased threat conditions. In combination these studies provide important new evidence to suggest that multi-directional perturbations are necessary to fully explore aspects of both normal, pathological and psychological influences on postural reactions in man.
Keywords: Harvested from Collections Canada